By Scripture and Plain Reason: A historical retrieval of the relationship between faith and reason to better engage with present-day secularism - Daniël J. Maritz (In die Skriflig, 2023)
The formal principle of the Reformation, sola Scriptura, has sometimes been thought to imply that the Reformed minister and church member need not concern themselves with the use of reason and philosophy in matters of faith and theology. This misconstrued understanding of sola Scriptura led to a low regard for reason in matters of faith among Reformed folk. A low regard for reason, in turn, gave anti-intellectualism and fideism a foothold in local Reformed churches and left secularism and its progressive ideas unchallenged as it infiltrated the minds of Reformed church members, especially at churches in bigger cities and close to universities. This phenomenon can be addressed by establishing apologetics training platforms at local Reformed churches where church members can be trained to better defend the truth against secularism. To establish apologetics on a local church level, however, one must first retrieve the correct role of reason in matters of faith. This article accordingly embarked on an historical retrieval within the broad Reformed tradition. Different Reformers and subsequent Reformed theologians were examined to retrieve the proper relationship between faith and reason. This was accompanied by a focus on other relevant themes such as the concept of common notions and the three acts of the intellect. Through an historical retrieval, this article consulted the primary sources of figures in the Reformed tradition spanning from the early 1500s to the early 1700s. Additionally, modern interpreters of these figures have also been introduced for their insights. It became evident that reason plays a ministerial role in matters of faith. Moreover, the concept of common notions establishes a grounding for the undeniable role of reason in dialogues with secularism. By introducing the three acts of the intellect, the discussion also moved on to function as a critique of mainstream secularism, as it pertains to its disordered approach to reality in the form of expressive individualism. Although this article is the first of two in a series, it nevertheless accomplished its own end to emphasise the need for apologetics on a local church level and to retrieve the role of reason in matters of faith.